ln(x*2+5x+6)=ln(x+11)

Simple and best practice solution for ln(x*2+5x+6)=ln(x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x*2+5x+6)=ln(x+11) equation:


Simplifying
ln(x * 2 + 5x + 6) = ln(x + 11)

Reorder the terms for easier multiplication:
ln(2x + 5x + 6) = ln(x + 11)

Reorder the terms:
ln(6 + 2x + 5x) = ln(x + 11)

Combine like terms: 2x + 5x = 7x
ln(6 + 7x) = ln(x + 11)
(6 * ln + 7x * ln) = ln(x + 11)
(6ln + 7lnx) = ln(x + 11)

Reorder the terms:
6ln + 7lnx = ln(11 + x)
6ln + 7lnx = (11 * ln + x * ln)
6ln + 7lnx = (11ln + lnx)

Solving
6ln + 7lnx = 11ln + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-11ln' to each side of the equation.
6ln + -11ln + 7lnx = 11ln + -11ln + lnx

Combine like terms: 6ln + -11ln = -5ln
-5ln + 7lnx = 11ln + -11ln + lnx

Combine like terms: 11ln + -11ln = 0
-5ln + 7lnx = 0 + lnx
-5ln + 7lnx = lnx

Add '-1lnx' to each side of the equation.
-5ln + 7lnx + -1lnx = lnx + -1lnx

Combine like terms: 7lnx + -1lnx = 6lnx
-5ln + 6lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-5ln + 6lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-5 + 6x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-5 + 6x)' equal to zero and attempt to solve: Simplifying -5 + 6x = 0 Solving -5 + 6x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 6x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = 0 + 5 6x = 0 + 5 Combine like terms: 0 + 5 = 5 6x = 5 Add '-6x' to each side of the equation. 6x + -6x = 5 + -6x Combine like terms: 6x + -6x = 0 0 = 5 + -6x Simplifying 0 = 5 + -6x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -3(5x+3)-(x-3)= | | 2.5x+5=20-3x | | 15c+7w=47 | | 18x^2+48x-96= | | Y=-14+6x | | 5n-3=29+n | | X-5.2=1.92 | | 3y+4r=5y+7r | | x-7/3=-21 | | E/9=6 | | 5(5x+5)+5(5x-2)= | | 8x+2=6x-28 | | 240=4xX+40 | | -2y+4=5y+6y | | -394/4=-401/4-c | | .5p-3.45=-1.2 | | 3(2x-5)+31=15 | | 5x-9+11x-8= | | y=20x+-20 | | 3.9x=2.4x+13.5 | | 3x^3=5x | | -(3x-3)-5(5x+3)= | | -11.1s=-16s-8.33 | | 4x-2=n-8 | | -x-5=x+11 | | 28+(x-36)=180 | | 8y+3=4y+5y | | y=-3(x-7)*2+5 | | -3(3x-5)-3(4x+4)= | | 90+2x-16=180 | | 3(5x-2)-3(x+4)= | | 12-(-7)-8= |

Equations solver categories